2010
DOI: 10.3102/1076998609337138
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Heterogeneity in Relationships Between Initial Status and Rates of Change: Treating Latent Variable Regression Coefficients as Random Coefficients in a Three-Level Hierarchical Model

Abstract: In studies of change in education and numerous other fields, interest often centers on how differences in the status of individuals at the start of a period of substantive interest relate to differences in subsequent change. In this article, the authors present a fully Bayesian approach to estimating threelevel Hierarchical Models in which latent variable regression (LVR) coefficients capturing the relationship between initial status and rates of change within each of J schools (Bw j , j ¼ 1,. .. , J) are trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 50 publications
1
36
0
2
Order By: Relevance
“…Using fully Bayesian estimation can provide more precise and robust estimates for parameters in a more complex model, such as with LVR models, as long as prior distributions are appropriately chosen. Choi and Seltzer (2010) found that uniform priors, which are analogous to inverse-Pareto distributions for the level-2 LVR variance components, resulted in less bias than using default inverse-gamma distributions. These results assist future researchers when selecting the best prior distributions to use for a threelevel LVR analysis.…”
Section: List Ofmentioning
confidence: 98%
See 3 more Smart Citations
“…Using fully Bayesian estimation can provide more precise and robust estimates for parameters in a more complex model, such as with LVR models, as long as prior distributions are appropriately chosen. Choi and Seltzer (2010) found that uniform priors, which are analogous to inverse-Pareto distributions for the level-2 LVR variance components, resulted in less bias than using default inverse-gamma distributions. These results assist future researchers when selecting the best prior distributions to use for a threelevel LVR analysis.…”
Section: List Ofmentioning
confidence: 98%
“…Therefore, more hypotheses about growth trajectories can be tested by using the more flexible LVR framework. Choi and Seltzer (2010) presented a fully Bayesian approach to estimate a threelevel LVR model with purely clustered data, and conducted a small simulation study to evaluate the differences in the choice of prior distributions for the level-2 random effects' variance components. Using fully Bayesian estimation can provide more precise and robust estimates for parameters in a more complex model, such as with LVR models, as long as prior distributions are appropriately chosen.…”
Section: List Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The effect of the differential performance of each student in the first assessment (November, 2005) compared to the mean for the population on the schools' growth rate (linear and quadratic) has been controlled. The reason for entering this predictor in the model is that several studies have related the differences in the students' initial performances to the different rates of change (Choi & Seltzer, 2005, 2010Klein & Muthén, 2006;Castro, Ruiz, & López, 2009). When calculating technical efficiency, the estimates of value added in mathematics and in reading comprehension calculated in the previous step are included as outputs of the education system.…”
Section: Inputs and Outputs Consideredmentioning
confidence: 99%